(untitled) (UNED Research Journal, 2019)
Introduction: e-learning is growing around the world exponentially and locally adapted applications or “apps” are useful. Objective: to learn if low performing students in a course about unidimensional and multidimensional structures would be motivated to learn with the help of an app. Methods: we applied a survey to students of Computing Logic who used the app. Results: each student prefers didactical materials which can be used within their mobile dispositive and rated the app positively. Conclusions: the app must have video tutorials, solved exercises, readings and podcasts, as well as a section to set daily goals that can motive students. Furthermore, they want to be able to choose learning options that produce the same final result; and both students and teachers need to get involved with the app.